PENGARUH VARIASI BERAT ROLLER CVT TERHADAP PERFORMA MOTOR INDIRECT INJECTION 125 CC DENGAN BAHAN BAKAR ETANOL 5% : EFFECT OF CVT ROLLER WEIGHT VARIATION ON THE PERFORMANCE OF A 125 CC INDIRECT INJECTION MOTORCYCLE USING 5% ETHANOL FUEL - Rahmad Agus Salim; Reonaldo Hartono; Hadi Rahmad; Deny Setiawan (Jurnal Teknik Mesin, 2026)
The performance of automatic motorcycles is influenced by the Continuously Variable Transmission (CVT), particularly the roller component that regulates the transmission ratio. The use of alternative fuels such as 5% ethanol (E5) is also relevant to improve energy efficiency and reduce emissions. This study analyzes the effect of roller weight variation on the power and torque of a 125 cc indirect injection motorcycle fueled with E5. The independent variable is roller weight (12 g, 15 g, 18 g), while the dependent variables are power (HP) and torque, with controlled variables including motorcycle type, fuel, and dynamometer. The experiment was conducted through dynotest and analyzed descriptively. Results show that 12 g rollers provide the best initial acceleration (9.82 HP at 7500 rpm), 15 g rollers are more stable at mid–high rpm (8.57 HP at 8000 rpm), and 18 g rollers produce the highest torque (9.27 Nm at 6000 rpm).